Cancer Screening Practices Among Healthcare Workers During the COVID-19 Pandemic - Datta, Geetanjali D.; Lauzon, Marie; Salvy, Sarah-Jeanne; Hussain, Shehnaz K.; Ghandehari, Sara; Merchant, Akil; Merin, Noah M.; Reckamp, Karen; Figueiredo, Jane C. (Frontiers in Public Health, 2022)
The COVID-19 pandemic has the potential to impact long-standing efforts to increase adherence to cancer screening guidelines. Healthcare workers (HCWs) experienced significant hardship, but generally have greater access to preventive services, making them a particularly relevant population in which to understand cancer screening behaviors during the pandemic. We report data from 794 HCWs enrolled in the NCI-funded Serological Sciences Network for Coronavirus Associations and Longitudinal Evaluation Study from December 2020-April 2021. Participants reported lifestyle and screening behaviors during relevant look-back periods which included the pandemic timeframe. Among women between the ages of 40 and 74, 25.7% were overdue for mammographic breast cancer screening. Among participants 50-75 years old, 38.9% were overdue for colorectal cancer screening. The proportion over-due varied according to race/ethnicity. Lifetime low-dose computed tomography lung cancer screening among HCWs age 50-80 years who were smokers was 10.9%. Strategies to address screening disruptions are needed to minimize the impact of later stage of diagnosis.